Studi Eksperimental Lendutan Pelat lantai Menggunakan Bata Hebel dengan Perkuatan Besi Siku - Deni Putra Arystianto; Fauzi Akbar Rahmawan; Kharisma Nur Cahyani; Harsalim Aimunandar Jayaputra (Jurnal Serambi Engineering, 2024)
This research examines the deflection behavior of floor slabs using Hebel blocks as the main material, reinforced with angle iron. The aim of this study is to understand how angle iron reinforcement can enhance the flexural capacity and stiffness of floor slabs made of Hebel blocks. The methodology involved experimental testing of 200 cm x 200 cm floor slabs using Hebel blocks measuring 20 cm x 60 cm x 7.5 cm and 5/5 angle iron reinforcement, with test loads applied through a water tank up to 250 kg/m². Deflection was measured using dial gauges at three different points: at both supports and the mid-span of the slab. The results of the study showed that the use of angle iron significantly improved the slab's stiffness and load-bearing capacity, with a uniform distribution of deflection. The largest deflection occurred at the mid-span, with an average dial 2 reading of 3.284 mm and a maximum deflection of 5.25 mm. Meanwhile, deflection at the supports showed average readings of 2.958 mm on dial 1 and 2.0978 mm on dial 3. This indicates that the deflection at the mid-span experienced the maximum load and deflection. The deflection at the supports, as measured by dials 1 and 3, was relatively symmetrical. The allowable deflection calculated based on SNI 2847-2019 is 11.11 mm or 16.67 mm, indicating that the slab deflection remains within safe limits.